Possible sarcopenia and depression among middle-aged and older adults in China: A 9-year longitudinal survey. - Xiang-Yang He; Zheng Liu; Zhi-Wei Lu; Ren-Cheng Zhao; Yan-Fang Guo; Qing Yuan; Li Huang; Xing-Lin Zhong (PLoS ONE)
Possible sarcopenia (PS) and depression are prevalent among middle-aged and older adults. However, few studies have evaluated the causal association between depression and PS, as well as its components. This study conducted both cross-sectional and longitudinal analyses to explore the relationship between PS and depression in a population aged 45 and oledr. We evaluated the association between PS and its components with depression using data from the China Health and Retirement Longitudinal Study (CHARLS). PS was assessed according to the Asian Working Group for sarcopenia gudielines established in 2019 (AWGS 2019). Depression was measured by the validated 10-item Center for Epidemiological Studies Depression Scale (CES-D.10), with a cut-off score of 12 or higher indicating the presence of depression. 10,058 participants included in cross-sectional study and 5,726 participants without depression from the same cohort in 2011 were followed through 2020. Logistic regression and Cox proportional hazards models were employed to assess the association between PS and its components with depression. Restricted cubic spline (RCS) model was utilized to evaluate dose-response relationshipbetween muscle strength and physical performance with depression, and subgroup analyses were performed to validate the robustness of the findings. Cross-sectional analysis revealed that the prevalence of PS among middle-aged and older adults was 32.84% (3,303/10,058). Both PS (OR:1.47,95%CI:1.34-1.63), low muscle strength (LMS) (OR:1.46,95%CI:1.24-1.71) and low physical performance (LPP) (OR:1.45,95%CI:1.31-1.61) exhibited higher odds of depression after adjusting covariates. 1515 cases (26.46%) of incident depression were identified during the 9-years follow-up. Subjects with PS (HR:1.10,95%CI:1.01-1.19), LMS (HR:1.16,95%CI:1.01-1.34) and LPP (HR:1.08,95%CI:1.01-1.18) were at an elevated risk of new-onset depression compared to those without these conditions. The RCS analysis demonstrated a non-linear relationship between muscle strength and physical performance with depression (p > 0.05). Participants aged 50-59, married, with education below middle school, living in rural areas, non-smokers or non-drinkers, sleeping less than 8 hours, and classified as obese exhibited an increased risk in subgroup analysis. (all p <  0.05). PS, LMS and LPP were indentified as independent risk factors for new-onset depression. It is essential to assess muscle strength and physical performance in community-dwelling middle-aged and older adults using simple and feasible objective measures to enhance depression screening.